2010
DOI: 10.1017/s0021859610000481
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and agriculture: introductory editorial

Abstract: There seems to be little doubt that the global climate is changing, partly due to natural factors, and in part due to forcing by human activities. However, there are still uncertainties about the extent to which human activity (including agricultural activity) has contributed to the current changes and could influence the future climate. Inevitably, climate and its variability, including the ongoing current changes at various spatial and temporal scales, must impact on agricultural activities. A major challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…Can these seed yield increases continue given that climate change will have direct impacts on land, water, temperature, atmospheric CO 2, and weather patterns [7]? These changes must impact agricultural activities [8], although there is debate as to whether the impacts will be negative or positive. Some authors [9,10] concluded that the overall impact of climate change on agriculture is expected to be negative, threatening global food security, whereas others (e.g., [11]) considered that global crop production could increase by approximately 50% by 2050 without extra land.…”
Section: Introductionmentioning
confidence: 99%
“…Can these seed yield increases continue given that climate change will have direct impacts on land, water, temperature, atmospheric CO 2, and weather patterns [7]? These changes must impact agricultural activities [8], although there is debate as to whether the impacts will be negative or positive. Some authors [9,10] concluded that the overall impact of climate change on agriculture is expected to be negative, threatening global food security, whereas others (e.g., [11]) considered that global crop production could increase by approximately 50% by 2050 without extra land.…”
Section: Introductionmentioning
confidence: 99%
“…This according to Eitzinger et al (2010) is due to anthropogenic and natural factors. Smith and Olesen (2010) described the emissions of greenhouse gases from agricultural systems as likely sources of global temperature increase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that pyramiding of significant traits/alleles at both stages is required for developing salt tolerant rice cultivars (Moradi et al, 2003). Besides, present global warming by increasing temperature necessitates identification of source of rice lines with more efficient alleles in order to tolerate adverse effects of climate change (IPCC, 2007;Eitzinger et al, 2010). In this study, three rice lines (Marishal, Kamini and Talmugra) were selected as highly tolerant under salinity (12 dS m -1…”
Section: Discussionmentioning
confidence: 99%
“…In inland areas, salt deposition is expected to increase as a consequence of increased evapotranspiration and water shortage with rising temperatures. Moreover, the earth's climate is predicted to still warm by an average of 2-4°C by the end of the 21 st century due to both anthropogenic and natural factors (IPCC, 2007;Eitzinger et al, 2010). In this context, rice breeders are being insisted for the need of further enhancement in tolerance or combination of more than one trait in rice cultivars in order to increase rice production under changing climate for fulfilling rapidly growing food demands of increasing human population.…”
Section: Introductionmentioning
confidence: 99%